2005
DOI: 10.1038/sj.onc.1208805
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 mitogen-activated kinase and c-Jun terminal kinase in migration response to lysophosphatidic acid and sphingosine-1-phosphate in glioma cells

Abstract: A potential role for 1-oleoyl-sn-glycero-3-phosphate or lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P) in the regulation of malignant diseases has been widely considered. In this study, we found that in transformed astroglial cells, the expression profile of lysophospholipid receptor mRNA and the action modes of LPA and S1P on cell motility were changed: there was a change in the acquisition of the ability of LPA to stimulate cell migration and a change in the migratory response to S1P from stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 54 publications
(59 reference statements)
6
73
2
Order By: Relevance
“…As previously reported [19,25], S1P 2 stimulation led to decreased motility of glioma cells. In contrast, S1P stimulation of this receptor subtype caused an increased invasiveness of glioma cells through Matrigel.…”
Section: Discussionsupporting
confidence: 85%
“…As previously reported [19,25], S1P 2 stimulation led to decreased motility of glioma cells. In contrast, S1P stimulation of this receptor subtype caused an increased invasiveness of glioma cells through Matrigel.…”
Section: Discussionsupporting
confidence: 85%
“…It has been reported that LPA activates many signaling pathways including the Ras/MEKK/MAPK, p38 MAPK, and JNK pathways (Bian et al, 2004;Malchinkhuu et al, 2005). It also has been reported that LPA stimulates DNA synthesis via activation of PI3K (Koh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Occupation by LPA in its cognate receptors triggers activation of various signaling molecules during cell migration. For example, LPA activates the Ras/MEKK/MAPK pathway, p38 MAPK, and JNK (Bian et al, 2004;Malchinkhuu et al, 2005). It has been reported that PI3K is also activated by LPA stimulation through two different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cytokines, the present study suggested a critical role of LPA in inflammatory responses in RA. Ki16425 has recently been shown to inhibit the migration and proliferation of cancer cells (18,(33)(34)(35) and smooth muscle cells (36) in vitro and of bone metastasis of ovarian and breast cancer cells in vivo (35). Thus, Ki16425 has been suggested to have potential as a therapeutic drug for cancer and vascular diseases.…”
Section: Discussionmentioning
confidence: 99%